Stereotactic Body Radiotherapy for Extracranial Oligometastatic Renal Cell Carcinoma: State of the Art and Future Perspectives - Sander Vandaele MD; Maarten Albersen MD, PhD; Benoit Beuselinck MD, PhD; Karolien Goffin MD, PhD; Vincent Vandecaveye MD, PhD; Henri Vandermeulen MD; Charlien Berghen MD, PhD (Technology in Cancer Research & Treatment, 2025)
Traditionally, radiotherapy in metastatic renal cell carcinoma (RCC) was applied for the palliation of symptoms and the control of critical sites such as bone lesions and brain metastases. However, technological advances in radiotherapy (RT) planning and delivery made it possible to precisely deliver high dose radiotherapy at a confined target volume. One such approach is stereotactic body radiotherapy (SBRT). In patients presenting with limited metastatic burden, known as oligometastatic RCC (omRCC), SBRT can be of interest to maintain local control, in order to defer the onset of either a first or a subsequent line of systemic treatment. In this narrative review, we summarize the prospective and retrospective evidence on SBRT as a treatment option for omRCC, and give insight into the future perspectives.